ChatGPT in Indonesian EFL Academic Writing: A Study of Critical Thinking and Creativity in Higher Education - Jihan Hikmah Awwaliyah Erfandy; Mukrim Mukrim; Moh Abraham Akbar Eisenring (Faculty of Education and Teacher Training of UIN Palopo, 2026)
The integration of ChatGPT into academic writing has raised important questions about its influence on students' cognitive processes, yet studies examining both critical thinking and creativity simultaneously in EFL contexts remain limited. This qualitative descriptive study explored students' perceptions of how ChatGPT influences their critical thinking and creativity in academic writing at Tadulako University, Central Sulawesi, Indonesia. Data were collected through semi-structured interviews with five purposively selected undergraduate students from the English Education Study Program who had experience using ChatGPT for academic writing tasks, and analyzed using Miles et al.'s (2014) qualitative procedures, guided by Facione's (1990) critical thinking framework and Torrance's (1966) creativity dimensions. The findings revealed three major themes: students engaged in active evaluative verification by cross-checking AI-generated content against academic sources; ChatGPT stimulated idea generation and topic exploration aligned with Torrance's dimensions of fluency and flexibility; and students consciously maintained their personal writing voice by paraphrasing and adapting AI outputs. The study concludes that ChatGPT can meaningfully support both critical thinking and creativity in academic writing when students engage with it reflectively and critically.